Cagnazzo Daniela Immacolata, Alcune note su Eschilo (?), P.OXY. XX 2247 - Cagnazzo, Daniela Immacolata (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2020)
This paper analyzes P.Oxy. XX 2247, which is attributed to Aeschylus on the paleographic basis. After a general presentation of the papyrus, a linguistic commentary is proposed, suggesting, where it is possible, some remarks and overall reconstruction of the context; moreover, we discuss elements that confirm the attribution of this work to Aeschylus.